Iron-catalyzed carbonylative cyclization of γ, δ-unsaturated aromatic oxime esters to functionalized pyrrolines. Issue 51 (27th May 2020) - Zhang, Youcan; Yin, Zhiping; Wang, Hai; Wu, Xiao-Feng
Abstract : A new method of iron-catalyzed carbonylative cyclization of γ, δ-unsaturated aromatic oxime esters to functionalized pyrrolines has been developed. Abstract : Herein, a new method of iron-catalyzed carbonylative cyclization of γ, δ-unsaturated aromatic oxime esters to functionalized pyrrolines has been developed. By using readily available substrates, 32 examples of functionalized pyrrolines were prepared in moderate to good yields. Notably, examples of reduction and cycloaddition reactions of the obtained product were given as well.